2021
DOI: 10.1002/ags3.12470
|View full text |Cite
|
Sign up to set email alerts
|

Current status of IBD and surgery of Crohn's disease in Thailand

Abstract: Inflammatory bowel disease (IBD) consists of two diseases: ulcerative colitis (UC) and Crohn's disease (CD). The incidence of IBD is much higher in Western countries compared to Asian countries, especially in Thailand. The incidence of UC in Thailand is quite low and seems less aggressive than in Western countries. Over the past two decades, the evolution of UC management in Thailand has led to a reduction in hospitalization and colectomy rate. Regarding CD, the majority of patients have an inflammatory phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
(86 reference statements)
2
5
0
2
Order By: Relevance
“…This discovery is consistent with previous results indicating that Bacteroidota, Firmicutes, Actinobacteriota, and Fusobacteriota are associated with obesity and that the obesity rate is significantly higher for immigrants than for people living in Thailand (Ley et al, 2006;Turnbaugh et al, 2009;Andoh et al, 2016). Furthermore, Desulfobacterota is shown to be related to inflammatory bowel diseases (Loubinoux et al, 2002), and the incidence of these diseases is much higher in Western countries compared to Asian countries, especially Thailand (Riansuwan and Limsrivilai, 2021), which is also consistent with our findings. These results again suggest that RSim normalization can improve the ability of differential abundance tests to control false discoveries and detect significant differences more effectively than existing normalization methods.…”
Section: Rsim Normalization Improves Accuracy Of Differential Abundan...supporting
confidence: 93%
“…This discovery is consistent with previous results indicating that Bacteroidota, Firmicutes, Actinobacteriota, and Fusobacteriota are associated with obesity and that the obesity rate is significantly higher for immigrants than for people living in Thailand (Ley et al, 2006;Turnbaugh et al, 2009;Andoh et al, 2016). Furthermore, Desulfobacterota is shown to be related to inflammatory bowel diseases (Loubinoux et al, 2002), and the incidence of these diseases is much higher in Western countries compared to Asian countries, especially Thailand (Riansuwan and Limsrivilai, 2021), which is also consistent with our findings. These results again suggest that RSim normalization can improve the ability of differential abundance tests to control false discoveries and detect significant differences more effectively than existing normalization methods.…”
Section: Rsim Normalization Improves Accuracy Of Differential Abundan...supporting
confidence: 93%
“…Current reports have indicated that surgery rates at 1 and 5 years in the postbiologic era are lower than those recorded in the prebiologic era (14.8% and 31.2% vs. 12.6% and 24.2%, respectively) 11,12 . Although no direct comparison has been made between Eastern and Western countries, the surgical rate is either compatible 13,14 or less in Eastern countries than that in Western countries 15,16 …”
Section: Temporal Trend Of CD Surgical Rate Indications and Methodsmentioning
confidence: 96%
“… 11 , 12 Although no direct comparison has been made between Eastern and Western countries, the surgical rate is either compatible 13 , 14 or less in Eastern countries than that in Western countries. 15 , 16 …”
Section: Temporal Trend Of CD Surgical Rate Indica...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory bowel diseases (IBD), such as Crohn’s disease and ulcerative colitis, are chronic recurrent intestinal disorders characterized by transmural granulomatous inflammation or mucosa and submucosa inflammation [ 1 ]. Although the exact cause of IBD is unknown, genetic factors, host intestinal flora, and the host immune system may play a role in IBD pathogenesis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%